COVID-19 And The Informal Sector In South Africa: Lessons, Challenges And Benefits - Malemela, Marry Selosebe; Selepe, Modupi (Innovation Journal of Social Sciences and Economic Review, 2025)
This paper examines the impact of the Covid-19 outbreak on informal trading in South Africa. This paper argues that the phenomenon of unemployment has always been a factor that pushes people to become informal traders, pre and post-COVID-19 outbreak in South Africa. However, as far as Covid-19 could have posed critical to the nation’s economy, this paper further asserts that the covid-19 brought major positive contributions to the citizenry, organizations and institutions in South Africa.  COVID-19 is said to have originated in China, and Wuhan in the year 2019 and later spread out across the globe to many countries and South Africa is not an exception.  The COVID-19 outbreak has forced the South African government to impose strict lockdown regulations to curb the spread. The outbreak of COVID-19 has, inter alia, influenced an increase in the unemployment rate and number of informal traders. Informal trading is the new norm in the post-COVID-19 era since different economic sectors were affected. Methodologically, this paper is conceptual in nature and it relies heavily on the existing literature to contribute to knowledge production with the discourse of the informal economy. The paper recommends that the South African government should come up with workable policies that will be effective even after the outbreak of any unforeseen circumstance like COVID-19. In essence, contingency plans must be in place and should be implemented timely. Workable policies can only be reached if informal traders become part of planning, decision making and implementations in the policy formulation process.
Keywords: COVID-19 Impact; Informal Trading; Unemployment; Lockdown Regulations; Sustainable Livelihoods; Contingency Planning; South Africa Economy